PENGARUH PERTUMBUHAN PENDAPATAN, KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BEI - Liong, Felix; Cherry, Irvania; Vanny, Sheyla Tri; Rahmi, Namira Ufrida; Yulisfan, Yulisfan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The purpose of this research is to analyze the effect of sales growth, dividend policy, debt policy and company’s size to infrastructure’s company value listed in Indonesia Exchange Stocks. The method of this research is clause method and use the purposive sampling method as the method to sampling the research’s population. The total of this research’s sample is 26 company. The result of the hypothesis test of the sales growth is the sales growth doesn’t affect the company’s value. The result is t-test 0.477 < t-table 1,666462. The result of the hypothesis test of the dividend policy is the dividend policy doesn’t affect the company’s value. The result is t-test 0.6389 < t-table 1,666462. The result of the hypothesis test of the debt policy is the debt policy affect the company’s value positively significant. The result is t-test 3,956 > t-table 1,666462. The result of the hypothesis test of the company’s size is the company’s size affect the company’s value positively significant The result is t-test 6,083 > t-table 1,666462. The result of simultaneously test is sales growth, dividend policy, debt policy, company’s size affects the company’s value, with the test result is F-test 5,607862 > F-table 2,332.